2019
DOI: 10.1021/acsnano.9b00089
|View full text |Cite
|
Sign up to set email alerts
|

Clear Wood toward High-Performance Building Materials

Abstract: Developing advanced building materials with both excellent thermal insulating and optical properties to replace common glass (thermal conductivity of ∼1 W m −1 K −1 ) is highly desirable for energy-efficient applications. The recent development of transparent wood suggests a promising building material with many advantages, including high optical transmittance, tunable optical haze, and excellent thermal insulation. However, previous transparent wood materials generally have a high haze (typically greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 44 publications
3
104
0
Order By: Relevance
“…Tensile tests present the same order of comparison of ultimate strength and modulus (Figure S17, Supporting Information). The mechanical performance of DW/PDMA–silica hybrids has been compared with other reported densified delignified woods [ 34,35 ] and polymer‐infiltrated delignified wood composites [ 37,51–53 ] (Table S2, Supporting Information). By integrating high amounts of inorganic constituents (≈45 wt%, TGA data in Figure S18 in the Supporting Information) in a hierarchical design, the strength and toughness of DW/PDMA–silica hybrids, either hot‐pressed or not, are higher than or comparable to most of purely polymeric wood‐based structural materials.…”
Section: Resultsmentioning
confidence: 99%
“…Tensile tests present the same order of comparison of ultimate strength and modulus (Figure S17, Supporting Information). The mechanical performance of DW/PDMA–silica hybrids has been compared with other reported densified delignified woods [ 34,35 ] and polymer‐infiltrated delignified wood composites [ 37,51–53 ] (Table S2, Supporting Information). By integrating high amounts of inorganic constituents (≈45 wt%, TGA data in Figure S18 in the Supporting Information) in a hierarchical design, the strength and toughness of DW/PDMA–silica hybrids, either hot‐pressed or not, are higher than or comparable to most of purely polymeric wood‐based structural materials.…”
Section: Resultsmentioning
confidence: 99%
“…Rough comparison of their 1.5 mm sample (∼40% haze) with our low haze TW (1.2 mm, 36% haze) puts both sets of data in a similar range for optical properties, although the present wood template volume fractions are higher (4.3 vol % compared with 2.9 vol %), and the wood structure is better preserved by not removing the most of the lignins and hemicelluloses. 15 , 18 …”
Section: Resultsmentioning
confidence: 99%
“…The lignin component in biomass can be removed through cooking/bleaching in NaOH/Na 2 SO 3 [53], NaClO 2 / glacial acetic acid [54], or H 2 O 2 /(acetic acid) steam [55]. Generally, the degree of delignification can be controlled by the processing time and temperature [56]. Hu et al found a welloriented cellulosic structure after the lignin and hemicellulose components of wood have been removed [57,58].…”
Section: Preparation Of Macroscopic Cellulose Productsmentioning
confidence: 99%